Efektivitas Penyuluhan Melalui Metode Ceramah Dan Media Lembar Balik Terhadap Perilaku Remaja Putri Tentang Pencegahan Anemia Di SMAN 14 Palembang - Yuli Hartati; Aulia Zahwa Maharani; Nurul Salasa Nilawati; Yunita Nazarena (Politeknik Negeri Jember, 2025)
Anemia is a condition of low hemoglobin levels in the blood that leads to a decrease in the number of red blood cells. It is the second leading cause of disability in the world and a global public health issue. In Palembang City, the prevalence of anemia among adolescent girls reached 26.5%. If left untreated, anemia can continue into adulthood and increase the risk of pregnancy complications, such as maternal death, premature birth, and low birth weight babies. One of the causes is the low behavior of adolescent girls regarding anemia prevention. This study aims to determine the effectiveness of counseling through lecture method and flipchart media on the behavior of adolescent girls about anemia prevention at SMAN 14 Palembang. The study used a quasi-experimental design with a two group pretest-posttest design on 70 female students of class X and XI, who were randomly divided into two groups, namely lecture and flipchart. Results showed an increase in knowledge, attitudes, and actions in both groups after counseling. In the lecture group, knowledge increased from 61.43 to 77.43, attitude from 54.29 to 74.71, and action from 78.43 to 89.14. In the flipchart group, knowledge increased from 70.57 to 82.86, attitude from 59.00 to 75.29, and action from 79.29 to 89.71. Wilcoxon test showed p = 0.000 in all variables of both groups. Nutrition counseling through lecture method and flipchart media is effective in improving adolescent girls' behavior in anemia prevention.Thus, nutrition counseling through lectures and flip charts proved to be effective in improving adolescent girls' behavior related to anemia prevention. Keywords: adolescent girls, anemia, behavior, flipchart, lecture